Probability and statistics : a course for physicists and engineers - Mathai, A. M. (De Gruyter textbook, 2018)
This textbook offers an introduction to concepts of probability theory, probability distributions relevant in the applied sciences, as well as basics of sampling distributions, estimation and hypothesis testing. As the basis for courses on space and atmospheric science, remote sensing, geographic information systems, meteorology, climate and satellite communications at UN-affiliated regional centers, various applications of the formal theory are discussed as well. These include applied topics such as model building and experiment design.